The Prevalence of Trichuriasis in School-age Children in Asia: A Systematic Review - Ivan Elisabeth Purba; Vierto Irennius Girsang; Amila Amila; Toni Wandra (Poltekkes Kemenkes Palu, 2023)
Introduction: Trichuris trichiura, hookworms, and Ascaris lumbricoides are known as soil-transmitted helminths that commonly infect humans. Transmission is more common in areas with poor personal hygiene and environmental sanitation. Objectives: The aim of this study was to determine available information on the prevalence of T. trichiura infection in school-age children in Asia. This information can be used for additional studies to evaluate the prevalence and risk factors for T. trichiura infection locally that can inform regional control programs and look at laboratory examination techniques to diagnose this parasite disease. Methods: Multiple databases (Web of Science, PubMed, ProQuest, Scopus, and Google Scholar) were searched for literature on the trichuriasis prevalence published from 2011 to January 2021. Results: A total of 13,836 studies were identified through database searches. The included studies represent 16 countries, with the highest number of study conducted in Yemen. Conclusions: The prevalence of trichuriasis in school-age children was found to vary widely by country. The Kato-Katz technique was commonly used to detect T. trichiura eggs in school-age children in Asia. Health sector should implement surveillance programs, particularly in countries with high infection prevalence. Educational programs aimed at improving personal hygiene and environmental sanitation to decrease trichuriasis transmission.